2020
DOI: 10.1002/esp.4831
|View full text |Cite
|
Sign up to set email alerts
|

High‐latitude dust deposition in snow on the glaciers of James Ross Island, Antarctica

Abstract: High‐latitude dust (HLD) depositions on four glaciers of James Ross Island (the Ulu Peninsula) were analysed. The deposition rate on the selected glaciers varies from 11.8 to 64.0 g m−2, which is one order of magnitude higher compared to the glaciers in Antarctica or elsewhere in the world. A strong negative relationship between the sediment amount and altitude of a sampling site was found. This is most likely caused by the higher availability of aeolian material in the atmospheric boundary layer. General sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Long-range transport of dust originating in Patagonia was observed during aerosol measurements (Kavan et al, 2018). Higher proportion of long range transported dust was found in snow pits on higher elevated glaciers compared to higher proportion of locally transported dust in lower elevated glaciers (Kavan et al, 2020b). Kňažková et al (2020) identified redistribution of mineral material within the HLD source area in Abernethy Flats impacting the local microtopography.…”
Section: James Ross Island Ulu Peninsulamentioning
confidence: 94%
“…Long-range transport of dust originating in Patagonia was observed during aerosol measurements (Kavan et al, 2018). Higher proportion of long range transported dust was found in snow pits on higher elevated glaciers compared to higher proportion of locally transported dust in lower elevated glaciers (Kavan et al, 2020b). Kňažková et al (2020) identified redistribution of mineral material within the HLD source area in Abernethy Flats impacting the local microtopography.…”
Section: James Ross Island Ulu Peninsulamentioning
confidence: 94%
“…Perennial snow banks are commonly formed in the lee of slopes where strong prevailing winds deposit aeolian transported snow. Melt from these snow banks often feed ephemeral streams and ephemeral to perennial lakes or ponds (Davies et al, 2013;Kavan et al, 2017Kavan et al, , 2020.…”
Section: Glacier Ice and Snowmentioning
confidence: 99%
“…Previously mapped geological structures (Mlčoch et al, 2020) were used to determine the limits of the present erosional surfaces of the Cretaceous to Neogene basement rocks. The poorly consolidated Cretaceous strata are easily weathered and reworked by ice masses on Ulu Peninsula, as well as by ephemeral streams or wind activity (Carrivick et al, 2012;Kavan et al, 2017Kavan et al, , 2020.…”
Section: Geological Map Componentsmentioning
confidence: 99%
“…The whole James Ross Archipelago lies in the precipitation shadow of the Antarctic Peninsula, with annual precipitation estimates of 300–500 mm of the water-equivalent (van Lipzig et al 2004). Importantly, high-speed winds have been observed to redistribute snow accumulations from flat surfaces and depressions (Kavan et al 2020).…”
Section: Study Areamentioning
confidence: 99%